The Functional Status of Patients with AIDS Attending Antiretroviral Treatment Center - Thejus, TJ (Medknow Publications, 2009)
AIMS: To assess the functional status of patients with Acquired immunodeficiency syndrome (AIDS) registered in the Anti-Retroviral Treatment (ART) center. MATERIALS AND METHODS: Design: Descriptive study. Study setting: ART center in Calicut Medical College, Kerala, India. Subjects: Cohorts of AIDS patients attending the ART center during the year 2007. Data collection: Done prospectively from the secondary data available from the center. Outcome measures: The demographic, morbidity, functional status and laboratory parameters were collected. Data processing was done using Excel datasheet and analysis were done using Epi info 2003. RESULTS: One hundred and ninety-five patients received care during this period; 69% were males. The mean age was 38±9 years; 80% of them were married and in 50% of their spouses also tested positive for HIV. The mean CD4 count was 127 cells/microliter. The majority (90%) were categorized as WHO Stage 3 or 4 of HIV. Only 52% of them were able to perform their usual work in or outside their house; the rest were not able to lead an economically productive life. Thirty-six per cent were only able to perform activities of daily living; 12% were bedridden. The functional status of the patients positively correlated with WHO disease stage (P = < 0-0001), and CD4 count and hemoglobin levels negatively correlated with staging (P = <0.001). 62% are having any of the opportunistic infections. CONCLUSION: Fifty per cent of the AIDS patients are disabled and need support and care. As AIDS is a growing problem, community-based palliative care for AIDS patients should be strengthened in India.